Maraknya Fear of Missing Out dan Media Sosial di Kalangan Remaja - Dwiputri, Masayu Nandhia; Suryaningtyas, Dewi; Hertisyahrani, Eka; Hariyadi, Muhammad Husin (Universitas Muria Kudus, 2022)
Self-esteem and self-regulation in a person play an important role in overcoming the desire to keep up with life that is constantly